A Study of Self-Efficacy, Intrinsic Needs, Interests, and Teaching Goal as They Relate to Teacher Instructional Behaviors. - Jaiboon, Pranee; Panthong, Kanok; Pradujprom, Piyathip (Saengtham College Journal, 2020)
The research purposes were 1) to confirm the factors of self-efficacy, intrinsic needs, interests, teaching goals, and teacher instructional behaviors variable 2) to study multiple correlations of self-efficacy, intrinsic needs, interests, teaching goals, and teacher instructional behaviors variable 3) to build multiple regressions of teacher instructional behaviors with self-efficacy, intrinsic needs, interests, and teaching goals variable. Samples: 157 teachers by proportional stratified random sampling and 1,570 questionnaires’ students by simple random sampling. Research instruments are teacher’s questionnaire and student’s questionnaire. Data were analyzed by confirmatory factor analysis, multiple correlation analysis, and multiple regressions analysis. The research findings were 1) self-efficacy, intrinsic needs, interests, teaching goals, and teacher instructional behaviors have construct validity 2) predictor variable: self-efficacy, intrinsic needs, interests, and teaching goals; and criterion variable: teacher instructional behaviors have significant correlation. 3) self-efficacy, intrinsic needs, interests, and teaching goals could be used to teacher instructional behaviors coping at 25.60%. The multiple regression equations were as follows: Multiple regressions in the form of raw score was: TIB = .744 + .154(SE)** + .151(IN)** + .103(INT)* + .157(TG)** Multiple regressions in the form of standard score was: TIB = .154Z**SE + .151Z**IN + .103Z*INT + .157Z**TG **p <.01 *p <.05